2006
DOI: 10.1002/pssb.200564658
|View full text |Cite
|
Sign up to set email alerts
|

Observation of Zn vacancies in ZnO grown by chemical vapor transport

Abstract: We have used positron annihilation spectroscopy to study the vacancy defects in ZnO crystals grown by both the conventional and contactless chemical vapor transport (CVT and CCVT). Our results show that Zn vacancies or Zn vacancy related defects are present in as-grown ZnO, irrespective of the growth method. Zn vacancies are observed in CVT-grown undoped ZnO and (Zn,Mn)O. The Zn vacancies present in undoped CCVT-ZnO are the dominant negatively charged point defect in the material. Doping the material with As i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
21
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 13 publications
5
21
0
Order By: Relevance
“…Thus, isolated Zn I is unlikely to exist in the annealed ZnO. Positron annihilation lifetime studies have confirmed the existence of both Zn and O vacancies in CVT grown ZnO [37][38][39]. Our combination results of XRD and PL suggest that O V is possibly trapped at the grain boundary in the ZnO sample with poor lattice perfection.…”
Section: Discussionsupporting
confidence: 78%
“…Thus, isolated Zn I is unlikely to exist in the annealed ZnO. Positron annihilation lifetime studies have confirmed the existence of both Zn and O vacancies in CVT grown ZnO [37][38][39]. Our combination results of XRD and PL suggest that O V is possibly trapped at the grain boundary in the ZnO sample with poor lattice perfection.…”
Section: Discussionsupporting
confidence: 78%
“…However, after annealing, the violet PL band decreased in intensity but it did not vanish completely. Tuomisto et al [44] confirmed by positron annihilation spectroscopy that the concentration of V Zn -or V Znrelated complexes is sufficiently high (410 16 cm À3 ) in the ZnO crystals grown both the zinc-rich and oxygen-rich conditions. Chen et al have also observed V Zn -related defects in hydrothermal grown ZnO crystals by positron annihilation spectroscopy and found that they can be removed by annealing above 600 1C [45].…”
Section: Article In Pressmentioning
confidence: 74%
“…It has an average value of τ 2 = 230 ± 15 ps. As in our earlier work on the as-grown samples [6], this component can be attributed to positrons annihilating as trapped at Zn vacancies [4,5].…”
Section: Methodsmentioning
confidence: 90%